2020
DOI: 10.25259/sni_588_2019
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intra-arterial indocyanine green angiography for the microsurgical treatment of dural arteriovenous fistula: A case report

Abstract: Background: In this study, we report a case of dural arteriovenous fistula (dAVF) that was successfully treated using intra-arterial indocyanine green (IA-ICG) videoangiography during open surgery. Moreover, the findings of IA-ICG videoangiography were compared with those of intraoperative digital subtraction angiography (DSA). Case Description: A 72-year-old male patient with a history of hypertension, hyperlipidemia, and thrombocytosis presented with generalized seizure. DSA revealed Cognard Type III dAVF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Marescaux et al reported ICG fluorophore through IA injection coupled with near-infrared laparoscopes to rapidly identify unsharp gastrointestinal bleeding territory in the porcine model; this minimally invasive approach revealed a precise definition of the bleeding source and reduced the surgical trauma during surgery . Similarly, Tominaga et al verified that IA-based ICG fluorescence angiography is a more sensitive intraoperative imaging tool for dural arteriovenous fistula surgery, which is due to clear visualization of vascular structures …”
Section: Interventional Fluorescence Imaging In Preclinical and Clini...mentioning
confidence: 99%
See 1 more Smart Citation
“…Marescaux et al reported ICG fluorophore through IA injection coupled with near-infrared laparoscopes to rapidly identify unsharp gastrointestinal bleeding territory in the porcine model; this minimally invasive approach revealed a precise definition of the bleeding source and reduced the surgical trauma during surgery . Similarly, Tominaga et al verified that IA-based ICG fluorescence angiography is a more sensitive intraoperative imaging tool for dural arteriovenous fistula surgery, which is due to clear visualization of vascular structures …”
Section: Interventional Fluorescence Imaging In Preclinical and Clini...mentioning
confidence: 99%
“…26 Similarly, Tominaga et al verified that IA-based ICG fluorescence angiography is a more sensitive intraoperative imaging tool for dural arteriovenous fistula surgery, which is due to clear visualization of vascular structures. 27 Due to selective uptake by the liver and unique metabolic characteristics, ICG is particularly suitable for HCC resection. For instance, Wang et al reported the IVR-aided selective intra-arterial injection technique for ICG fluorescence-based positive staining of hepatic segmentation during laparoscopic surgery, verifying the feasibility of real-time imaging-guided demarcation and definition of the resection line for targeted liver segments.…”
Section: Indocyanine Greenmentioning
confidence: 99%
“…Since synchronization easily occurs at the anastomotic vessels when the indocyanine green flows to the cortical vessels through the carotid artery, the contrast in the imaging area is not abundantly clear, which affects the afterward assessment of results. Currently, although arterial injection of ICG has been applied to treat peripheral cerebral aneurysms, spinal arteriovenous fistulas, and dural arteriovenous fistulas (9)(10)(11), there have been few reports about the use of superselective arterial injection of ICG to estimate the patency of the anastomotic site during bypass surgery (12). Thus, this study attempts to estimate the patency of the anastomotic site after cerebral blood flow reconstruction by superselective injection of ICG into the superficial temporal artery through a catheter (select right femoral artery and apply a 5F curved catheter), and investigate the feasibility and effects of this method.…”
Section: Introductionmentioning
confidence: 99%